Pengaruh Brand Ambassador Shenina Cinnamon dan Brand Awareness Barenbliss Terhadap Pembelian pada Followers Instagram@Barenbliss_ID - Novia Fitriani, Adelarita; Marhaeni Kurdaningsih, Dian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the effect of brand ambassador shenina cinnamon and brand awareness barenbliss on purchases on Instagram followers @barenbliss_id because the cosmetics industry in Indonesia is increasingly competitive, many local brands choose Brand Ambassadors from Korea. However, Barenbliss takes a different approach by using a local Brand Ambassador, who better represents the character of Indonesian women with the AIDA (Attention, Interest, Desire, Action) theory approach. This research method uses a quantitative approach. The results of this study indicate that the validity test of all questionnaire items is declared valid with a value of r_hitung> r_tabel (0.195), and all items are declared reliable with r_hitung> r_tabel (0.600). The results of the Multiple Linear Regression analysis test show that Brand Ambassador (X1) has a significant influence on Purchasing (Y), with a significant value below 0.000 <0.05. And there is a significant influence of Barenbliss Brand Awareness (X2) on Purchases (Y), with a significant value of 0.000<0.05. This study concludes that the role of Brand Ambassador Shenina Cinnamon and strengthening Barenbliss Brand Awareness is an effective strategy in increasing consumer purchases of Barenbliss cosmetic products. The limitation in this study lies in the limited scope of respondents, it is hoped that further research can involve a more diverse sample so that the results are more comprehensive more broadly.